2019
DOI: 10.1001/jamaneurol.2019.2137
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Neurofilament Light Chain Levels and Long-term Disease Course Among Patients With Multiple Sclerosis Followed up for 12 Years

Abstract: Blood sample-based biomarkers that are associated with clinically meaningful outcomes for patients with multiple sclerosis (MS) have not been developed.OBJECTIVE To evaluate the potential of serum neurofilament light chain (sNFL) measurements as a biomarker of disease activity and progression in a longitudinal MS data set.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
165
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(187 citation statements)
references
References 42 publications
9
165
2
Order By: Relevance
“…Both serum and CSF NfL levels have been consistently associated with long-term brain atrophy. 33,34 Of note, this effect size is similar to the percentage of variance explained for the associations between CHIT1 and disease activity measures in our work. In contrast, serum and CSF NfL levels measured at 6 to 8 years of disease duration were not associated or were at most weakly associated with future relapse activity, EDSS worsening, or lesions in 2 recent large-scale studies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Both serum and CSF NfL levels have been consistently associated with long-term brain atrophy. 33,34 Of note, this effect size is similar to the percentage of variance explained for the associations between CHIT1 and disease activity measures in our work. In contrast, serum and CSF NfL levels measured at 6 to 8 years of disease duration were not associated or were at most weakly associated with future relapse activity, EDSS worsening, or lesions in 2 recent large-scale studies.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, serum and CSF NfL levels measured at 6 to 8 years of disease duration were not associated or were at most weakly associated with future relapse activity, EDSS worsening, or lesions in 2 recent large-scale studies. 33,34 Similarly, we did not detect an association between NfL levels at diagnosis and any primary outcome, and associations between CHIT1 and disease activity outcomes were importantly independent of NfL. A combination of biomarkers will likely be indicated to capture the different disease processes in MS.…”
Section: Discussionmentioning
confidence: 69%
“…13,14 Importantly, as shown by recent studies, pNfL concentrations at diagnosis also predict important longterm outcomes, such as brain atrophy and risk to achieve clinical disability milestones. 15,26 Whereas our data reveal differences in pNfL dynamics across the studied DMTs, we cannot rule out that differences had been achieved with a more complete model for the PS, even if our additional adjustments did not lead to major changes in the estimates. Notably, however, we did not have access to sufficiently precise MRI data, which are known to affect pNfL.…”
Section: Discussionmentioning
confidence: 71%
“…Recently, the UCSF-Epic cohort reported that at the 5-year follow-up, those treated with highly effective therapies experienced greater decreases in serum NFL compared with those on platform therapies, with a significant interaction found between NFL and EDSS. 61 This biomarker may also have utility in clinic as an adjunct to conventional MRI and may even have prognostic value at disease onset. However, further standardization and refinement of serum neurofilament testing is necessary before neurofilament can enter routine clinical use.…”
Section: The Reported Safety Profiles Of Some Highly Effective Agentsmentioning
confidence: 99%